Modal logic for philosophers - Garson, James W., 1943- (Cambridge ; New York : Cambridge University Press, 2006)
"Designed for use by philosophy students, this book provides an accessible yet technically sound treatment of modal logic and its philosophical applications. Every effort has been made to simplify the presentation by using diagrams in place of more complex mathematical apparatus."--Jacket
Introduction : what is modal logic? -- 1. The system K : a foundation for modal logic -- 2. Extensions of K -- 3. Basic concepts of intensional semantics -- 4. Trees for K -- 5. The accessibility relation -- 6. Trees for extensions of K -- 7. Converting trees to proofs -- 8. Adequacy of propositional modal logics -- 9. Completeness using canonical models -- 10. Axioms and their corresponding conditions on R -- 11. Relations between the modal logics -- 12. Systems for quantified modal logic -- 13. Semantics for quantified modal logics -- 14. Trees for quantified modal logic -- 15. The adequacy of quantified modal logics -- 16. Completeness of quantified modal logics using trees.
Includes bibliographical references (pages 445-448) and index.
Print version record.
English.
eBooks on EBSCOhost
Keywords: Modality (Logic) -- Textbooks; Modalité (Logique) -- Manuels d'enseignement supérieur.; PHILOSOPHY -- Logic; Modality (Logic); Modallogik; Textbooks; Lehrbuch